Simulated biomechanical effect of aspheric transition zone ablation profiles after conventional hyperopia refractive surgery - Ruirui Du; Lihua Fang; Binhui Guo; Yinyu Song; Huirong Xiao; Xinliang Xu; Xingdao He (Mathematical Biosciences and Engineering, 2021)
We studied the effects of the aspheric transition zone on the optical wavefront aberrations, corneal surface displacement, and stress induced by the biomechanical properties of the cornea after conventional laser in situ keratomileusis (LASIK) refractive surgery. The findings in this study can help improve visual quality after refractive surgery. Hyperopia correction in 1-5D was simulated using five types of aspheric transition zones with finite element modeling. The algorithm for the simulations was designed according to the optical path difference. Wavefront aberrations were calculated from the displacements on the anterior and posterior corneal surfaces. The vertex displacements and stress on the corneal surface were also evaluated. The results showed that the aspheric transition zone has an effect on the postoperative visual quality. The main wavefront aberrations on the anterior corneal surface are defocus, y-primary astigmatism, x-coma, and spherical aberrations. The wavefront aberrations on the corneal posterior surface were relatively small and vertex displacements on the posterior corneal surface were not significantly affected by the aspheric transition zone. Stress analysis revealed that the stress on the cutting edge of the anterior corneal surface decreased with the number of aspheric transition zone increased, and profile #1 resulted in the maximum stress. The stress on the posterior surface of the cornea was more concentrated in the central region and was less than that on the anterior corneal surface overall. The results showed that the aspheric transition zone has an effect on postoperative aberrations, but wavefront aberrations cannot be eliminated. In addition, the aspheric transition zone influences the postoperative biomechanical properties of the cornea, which significantly affect the postoperative visual quality.